Adipose tissue‐derived mesenchymal stem cells as monocultures or cocultures with human umbilical vein endothelial cells: Performance in vitro and in rat cranial defects. Issue 4 (4th June 2013) - Ma, Jinling; Both, Sanne K.; Ji, Wei; Yang, Fang; Prins, Henk‐Jan; Helder, Marco N.; Pan, Juli; Cui, Fu‐Zhai; Jansen, John A.; van den Beucken, Jeroen J. P.
Abstract: The aim of this study was to compare the osteogenic capacity between human adipose tissue‐derived mesenchymal stem cells (AT‐MSCs) and their cocultures with human umbilical vein endothelial cells (HUVECs) in vitro and their biological performance in vivo . First, the optimal cell ratio in cocultures for osteogenic differentiation was determined by seeding AT‐MSCs and HUVECs in ratios varying from 100:0 to 0:100 on tissue culture plates. Afterward, AT‐MSCs and AT‐MSCs/HUVECs (50:50) were seeded on porous titanium fiber mesh scaffolds (Ti) for both in vitro and in vivo osteogenic evaluation. For in vitro evaluation, cell osteogenic differentiation was assessed by alkaline phosphatase (ALP) activity and calcium assay. For in vivo evaluation, the scaffolds were implanted bilaterally into rat cranial defects (5 mm diameter) and bone formation was assessed histologically and histomorphometrically after 8 weeks. The ratio of 50:50 was chosen in the cocultures because this coculture condition retained similar amount of calcium deposition while using the least amount of AT‐MSCs. Moreover, AT‐MSCs showed higher osteogenic differentiation in comparison to AT‐MSCs/HUVECs on Ti in vitro . Furthermore, superior bone formation was observed in AT‐MSCs compared to AT‐MSCs/HUVECs in rat cranial defects. In conclusion, AT‐MSCs showed significantly higher osteogenic potential compared to AT‐MSCs/HUVECs both in vitro and in vivo . © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1026–1036, 2014.